Morphology, Geology and Water Quality Assessment of Former Tin Mining Catchment - Muhammad Aqeel Ashraf; Mohd. Jamil Maah; Ismail Yusoff (The Scientific World Journal)
Bestari Jaya, former tin mining catchment covers an area of 2656.31 hectares comprised of four hundred and forty-two different-size lakes and ponds. The present study area comprise of 92 hectares of the catchment that include four large size lakes. Arc GIS version 9.2 used to develop bathymetric map, Global Positioning System (GPS) for hydrographical survey and flow meter was utilized for water discharge analysis (flow routing) of the catchment. The water quality parameters (pH, temperature, electric conductivity, dissolved oxygen DO, total dissolved solids TDS, chlorides, ammonium, nitrates) were analyzed by using Hydrolab. Quality assurance (QA) and quality control (QC) procedures were strictly followed throughout the field work and data analysis. Different procedures were employed to evaluate the analytical data and to check for possible transcription or dilution errors, changes during analysis, or unusual or unlikely values. The results obtained are compared with interim national water quality standards for Malaysia indicates that water quality of area is highly degraded. It is concluded that Bestri Jaya ex-mining catchment has a high pollution potential due to mining activities and River Ayer Hitam, recipient of catchment water, is a highly polluted river.